Influence of sedimentary deposition on the microbial assembly process in Arctic Holocene marine sediments - Han, Dukki; Richter-Heitmann, Tim; Kim, Ji-Hoon; Friedrich, Michael W.; Yin, Xiuran; Elvert, Marcus; Ryu, Jong-Sik; Jang, Kwangchul; Nam, Seung-Il (Frontiers in Microbiology, 2023)
The sea-level rise during the Holocene (11–0 ky BP) and its resulting sedimentation and biogeochemical processes may control microbial life in Arctic sediments. To gain further insight into this interaction, we investigated a sediment core (up to 10.7 m below the seafloor) from the Chuckchi Shelf of the western Arctic Ocean using metabarcoding-based sequencing and qPCR to characterize archaeal and bacterial 16S rRNA gene composition and abundance, respectively. We found that Arctic Holocene sediments harbor local microbial communities, reflecting geochemical and paleoclimate separations. The composition of bacterial communities was more diverse than that of archaeal communities, and specifically distinct at the boundary layer of the sulfate-methane transition zone. Enriched cyanobacterial sequences in the Arctic middle Holocene (8–7 ky BP) methanogenic sediments remarkably suggest past cyanobacterial blooms. Bacterial communities were phylogenetically influenced by interactions between dispersal limitation and environmental selection governing community assembly under past oceanographic changes. The relative influence of stochastic and deterministic processes on the bacterial assemblage was primarily determined by dispersal limitation. We have summarized our findings in a conceptual model that revealed how changes in paleoclimate phases cause shifts in ecological succession and the assembly process. In this ecological model, dispersal limitation is an important driving force for progressive succession for bacterial community assembly processes on a geological timescale in the western Arctic Ocean. This enabled a better understanding of the ecological processes that drive the assembly of communities in Holocene sedimentary habitats affected by sea-level rise, such as in the shallow western Arctic shelves.